The role of the European Union in regulating corporate due diligence on Human Rights and the environmental issues (Revista de Estudios Europeos, 2026)
This paper analyzes in detail the role of the European Union in the regulation of corporate due diligence in the field of human rights and the environment. For this purpose, the paper is structured in three main blocks. Firstly, the evolution of the concept of due diligence in the European regulatory environment field is studied, including its background at the multilateral level, how it has been received within EU law and the first regulatory attempts in specific sectors such as timber or conflict minerals. Secondly, a detailed analysis will be made of the recently approved European Directive on due diligence, in particular its objectives, application mechanisms, obliged parties and liability regime.  Finally, the main challenges of its implementation will be addressed, paying particular attention to the challenges faced by Member States and companies themselves in the transposition and enforcement of these new obligations.
Keywords: Due diligence; Human Rights; Environment; European Union; Directive